PEREMPUAN DALAM KEARIFAN LOKAL SUKU BADUY - Maharani, Septiana Dwiputri (Jurnal Filsafat "WISDOM", 2009)
AbstractMany people call the Baduy is an ethnic group of Sundaneseliving in a relatively isolated area. In fact the Baduy peopleintentionally detach themselves from modernity. They overcome life problems by holding their custom order firmly. They maintain their nature, coexist harmoniously, and obey their tradition. They believe that if they do not obey it, surely, there will be an accident or difficulties in their life.The Baduy society consists of Inner Baduy and Outer Baduy.They place forward the harmonious relationship between men and women (husband and wife) with work sharing. The Baduy marriage also recognizes monogamy. The marriage partner is determined by father side, and the good marriage is in consanguinity. Divorce, according to the Inner Baduy, is only permitted by reason of death, whereas the Outer Baduy enable the divorce without reason of death. The Baduy women exist by making woven clothes. It shows that woman can work out of domestic affairs.Keyword: Baduy, Baduy woman, local wisdom, gender relation,harmony, monogamy.